Flame-retardant flexible solid electrolyte material and preparation method and application thereof

By adding a full fluoride polyetherol to the polymeter polymer to modify it, the flame retardant flexible solid electrolyte material is prepared, solving the problem of flammable and low -chamber temperature ion conductivity of traditional battery, and achieve higher safety performance. And ion conduct rate.

CN119381542AActive Publication Date: 2025-01-28DONGFENG MOTOR GRP

Patent Information

Application Number
CN202411402988.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-28
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The carbonate alkyl electrolytes of traditional lithium-ion batteries are flammable, and the solid polymer electrolytes are extremely flammable in the air, and ions are difficult to transport, resulting in safety hazards and low room temperature ion conductivity.

Method used

The high -molecular weight containing fluoride polymer is used as a substrate, and the full fluoride polyetherol is added to the basis to prepare the flame retardant flexible solid electrolyte material. The material is prepared through the mixed and thermal film formation process through the dense refiner, which has good flame retardability and increased ionic conductivity.

Benefits of technology

Improve the safety performance of lithium ion batteries and the ionic conductivity of the solid electrolyte film, ensure the high ion conduction capacity at high room temperature, while maintaining good flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381542A_ABST
    Figure CN119381542A_ABST
Patent Text Reader

Abstract

The invention relates to a flame-retardant flexible solid electrolyte material as well as a preparation method and application thereof, and belongs to the technical field of secondary batteries. The method comprises the following steps: dispersing lithium salt in perfluoropolyether alcohol to obtain a mixture; and modifying the fluorine-containing polymer by using the mixture to obtain the flame-retardant flexible solid electrolyte, the high-molecular-weight fluorine-containing polymer with good flame retardance is selected as a matrix, and the low polymer perfluoropolyether alcohol is added to modify the matrix, so that the whole solid electrolyte has relatively wide molecular weight distribution, the flexibility of the solid electrolyte is increased on the basis of ensuring the mechanical property, and the ionic conductivity and the processability of the polymer are improved. After the polymer electrolyte membrane is prepared into the solid electrolyte membrane, the solid electrolyte membrane has good flame retardance, and the ionic conductivity of the polymer electrolyte membrane is also improved while the safety performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a flame-retardant flexible solid electrolyte material and a preparation method and application thereof. Background Art

[0002] Traditional lithium-ion batteries generally use flammable alkyl carbonate electrolytes, which are at risk of thermal runaway due to extrusion, impact, short circuit and other reasons during operation, which can easily lead to safety accidents. Lithium-ion batteries using solid electrolytes have significantly improved safety because there is no problem of electrolyte volatilization and leakage. However, the mechanical properties of solid inorganic electrolytes are poor, so solid polymer electrolytes are mostly used. Common solid polymer electrolytes such as polyethylene oxide and polyurethane are extremely flammable in the air. Once the battery has thermal runaway, there are also safety hazards. In addition, polyethylene oxide has a regular structure and high crystallinity, which makes ion transport difficult. Most solid polymer batteries work under high temperature conditions (>50°C) to ensure that the polymer electrolyte has a high ionic conductivity, while the ionic conductivity at room temperature is generally low (about 10 -8 S / cm).

[0003] As a polymer matrix, high molecular weight fluorinated polymers have good mechanical properties, chemical stability and excellent flame retardancy. The presence of fluorine atoms in the polymer matrix improves the electrochemical stability window of solid-state batteries and greatly increases the probability of forming a dense and uniform solid electrolyte interface (SEI) layer. However, fluorinated polymers contain a high content of CF bonds, which determines that they have excellent solvent and chemical resistance, and their molecular weight is large, so their processing technology is relatively difficult and their ion conductivity is low. Summary of the invention

[0004] The present application provides a flame-retardant flexible solid electrolyte material and a preparation method and application thereof, which can improve the ionic conductivity of a polymer electrolyte membrane while improving safety performance.

[0005] In a first aspect, the present application provides a method for preparing a flame retardant flexible solid electrolyte material, the method comprising:

[0006] dispersing a lithium salt in a perfluoropolyether alcohol to obtain a mixture;

[0007] The mixture is used to modify the fluorine-containing polymer to obtain a flame-retardant flexible solid electrolyte.

[0008] As an optional embodiment, the structural formula of perfluoropolyether alcohol is:

[0009] Wherein, n is any positive integer.

[0010] As an optional embodiment, the number average molecular weight of the perfluoropolyether alcohol is 10 4 ~10 6 .

[0011] As an optional embodiment, the structural formula of the fluorine-containing polymer is:

[0012]

[0013] Among them, R f Selected from - CF 3 , -CF 2 CF 3 , -CF 2 CF 2 CF 3 and -CF 2 CF 2 CF 2 CF 3 At least one of;

[0014] X is selected from -COOH, -CN, -OC 6 F 5 At least one of .

[0015] As an optional embodiment, the number average molecular weight of the fluorine-containing polymer is 10 4 ~10 6 .

[0016] As an optional embodiment, the lithium salt includes at least one of lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide).

[0017] As an optional embodiment, the mass ratio of the fluorinated polymer to the perfluoropolyether alcohol is 10:(2-3); and / or

[0018] The mass ratio of the fluorine-containing polymer to the lithium salt is 10:(0.2-0.6).

[0019] As an optional implementation, the modification method is to use an internal mixer for mixing.

[0020] In a second aspect, the present application provides a flame retardant flexible solid electrolyte material, which is prepared by the method provided in the first aspect.

[0021] In a third aspect, the present application provides a solid electrolyte membrane, the components of which include the flame-retardant flexible solid electrolyte material provided in the second aspect.

[0022] As an optional implementation manner, the thickness of the solid electrolyte membrane is 50 μm to 200 μm.

[0023] In a fourth aspect, the present application provides a method for preparing a solid electrolyte membrane, the method comprising:

[0024] Obtaining the flame-retardant flexible solid electrolyte material provided in the second aspect;

[0025] As an optional implementation, the flame-retardant flexible solid electrolyte is subjected to hot pressing to form a film to obtain a solid electrolyte membrane.

[0026] The hot pressing temperature of the hot pressing film is 150°C to 230°C; and / or

[0027] The hot pressing pressure of hot pressing film forming is 15MPa to 20MPa; and / or

[0028] The hot pressing time of hot pressing film forming is 30s to 60s.

[0029] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0030] The method provided in the embodiment of the present application selects a high molecular weight fluorinated polymer with good flame retardancy as the matrix and adds oligomer perfluoropolyether alcohol to modify it, so that the entire solid electrolyte has a wide molecular weight distribution, increases its flexibility on the basis of ensuring mechanical properties, and improves ion conductivity and polymer processability. After it is prepared into a solid electrolyte membrane, the solid electrolyte membrane has good flame retardancy, improves safety performance and also improves the ion conductivity of the polymer electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0033] Figure 1 A schematic diagram of a process for a method provided in an embodiment of the present application;

[0034] Figure 2 This is a graph of the test results of the AC impedance of the solid electrolyte membrane provided in Example 1, Example 2 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0037] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the embodiment of the present application provides a method for preparing a flame retardant flexible solid electrolyte material, the method comprising:

[0038] S1. dispersing a lithium salt in a perfluoropolyether alcohol to obtain a mixture;

[0039] In some embodiments, the lithium salt may be selected from one of lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0040] In some embodiments, the structural formula of the perfluoropolyether alcohol is:

[0041] Wherein, n is any positive integer.

[0042] Furthermore, the number average molecular weight of the perfluoropolyether alcohol is 10 4 ~10 6 .

[0043] In some embodiments, the mass ratio of perfluoropolyether alcohol to lithium salt is (2-3):(0.2-0.6).

[0044] Exemplarily, the mass ratio of perfluoropolyether alcohol to lithium salt can be 2:0.4, 2.5:0.4, 3:0.4, 2.5:0.2, 2.5:0.6, 3:0.4 or 3:0.6, etc., and it can also be any value in the range of (2-3): (0.2-0.6).

[0045] S2. The fluorine-containing polymer is modified by using the mixture to obtain a flame-retardant flexible solid electrolyte.

[0046] In some embodiments, the fluoropolymer has the structural formula:

[0047]

[0048] Among them, R f Selected from - CF 3 , -CF 2 CF 3 , -CF 2 CF 2 CF 3 and -CF 2 CF 2 CF 2 CF 3 At least one of;

[0049] X is selected from -COOH, -CN, -OC 6 F 5 At least one of .

[0050] Furthermore, the number average molecular weight of the fluorinated polymer is 10 4 ~10 6 .

[0051] In some embodiments, the mass ratio of the fluorine-containing polymer to the perfluoropolyether alcohol is 10:(2-3).

[0052] Exemplarily, the mass ratio of the fluorinated polymer to the perfluoropolyether alcohol can be 10:2, 10:2.1, 10:2.2, 10:2.3, 10:2.4, 10:2.5, 10:2.6, 10:2.7, 10:2.8, 10:2.9 or 10:3, etc., and it can also be any value within the range of 10:(2-3).

[0053] In some embodiments, the mass ratio of the fluorine-containing polymer to the lithium salt is 10:(0.2-0.6).

[0054] For example, the mass ratio of the fluorine-containing polymer to the lithium salt may be 10:0.1, 10:0.2, 10:0.3, 10:0.4, 10:0.5 or 10:0.6, etc., and may also be any value within the range of 10:(0.2-0.6).

[0055] In some embodiments, the modification method is to use an internal mixer for mixing. The electrolyte film is prepared by internal mixing and hot pressing molding process without adding solvent, making the whole process more green and environmentally friendly.

[0056] This method uses a high molecular weight fluorinated polymer with good flame retardancy as the matrix and adds oligomer perfluoropolyether alcohol to modify it, so that the entire solid electrolyte has a wide molecular weight distribution, increases its flexibility on the basis of ensuring mechanical properties, and improves ion conductivity and polymer processability. After it is prepared into a solid electrolyte membrane, the solid electrolyte membrane has good flame retardancy, improves safety performance and also improves the ion conductivity of the polymer electrolyte membrane.

[0057] Based on a general inventive concept, an embodiment of the present application further provides a flame retardant flexible solid electrolyte material, and the flame retardant flexible solid electrolyte material is prepared by the method provided above.

[0058] The flame retardant flexible solid electrolyte material is prepared based on the above method. The specific steps of the method can refer to the above embodiment. Since the flame retardant flexible solid electrolyte material adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here one by one.

[0059] Based on a general inventive concept, an embodiment of the present application further provides a solid electrolyte membrane, the components of which include the flame-retardant flexible solid electrolyte material provided above.

[0060] The solid electrolyte membrane is realized based on the above-mentioned flame-retardant flexible solid electrolyte material. The specific content of the flame-retardant flexible solid electrolyte material can refer to the above-mentioned embodiment. Since the solid electrolyte membrane adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0061] In some embodiments, the solid electrolyte membrane has a thickness of 50 μm to 200 μm.

[0062] Exemplarily, the thickness of the solid electrolyte membrane can be 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm, etc., and it can also be any value within the range of 50μm to 200μm.

[0063] Based on a general inventive concept, the present application also provides a method for preparing a solid electrolyte membrane, the method comprising:

[0064] S1. Obtaining the flame-retardant flexible solid electrolyte material provided above;

[0065] S2. Hot-pressing the flame-retardant flexible solid electrolyte into a film to obtain a solid electrolyte membrane.

[0066] In some embodiments, the hot pressing temperature of the hot pressing film is 150° C. to 230° C.; the hot pressing pressure of the hot pressing film is 15 MPa to 20 MPa; and the hot pressing time of the hot pressing film is 30 s to 60 s.

[0067] Exemplarily, the hot pressing temperature of the hot pressing film can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C or 230°C, etc., and it can also be any value in the range of 150°C to 230°C. The hot pressing pressure of the hot pressing film can be 15MPa, 16MPa, 17MPa, 18MPa, 19MPa or 20MPa, etc., and it can also be any value in the range of 15MPa to 20MPa. The hot pressing time of the hot pressing film can be 30s, 35s, 40s, 45s, 50s, 55s or 60s, etc., and it can also be any value in the range of 30s to 60s.

[0068] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0069] Example 1

[0070] A solid electrolyte membrane, the preparation process of which is as follows:

[0071] 1. Weigh 2.0g of perfluoropolyether alcohol into a glass bottle, then move it into a glove box, and weigh 0.2g of lithium bis(trifluoromethanesulfonyl)imide and add it. Cover the bottle cap and place the glass bottle at room temperature with magnetic stirring for 1 hour to evenly disperse the lithium salt.

[0072] 2. Weigh 10.0g of fluorine-containing polymer and the above-mentioned perfluoropolyether alcohol and add them to an internal mixer for mixing to make the raw materials uniform. Add the uniformly mixed raw materials to a hot press and hot press them at 180°C and 20MPa for 40s to obtain a flame-retardant flexible solid electrolyte membrane (referred to as FFKM1-PFPE-OH-LiTFSI). Use a film press to cut the obtained electrolyte membrane into discs with a diameter of 16mm and place them in a glove box for standby use.

[0073] According to the measurement by a film thickness gauge, the thickness of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment is about 105um; the flame-retardant flexible solid electrolyte membrane prepared in this embodiment is subjected to a combustion test, and the test shows that the flame-retardant flexible solid electrolyte membrane prepared in this embodiment extinguishes itself immediately after leaving the fire.

[0074] The flame-retardant flexible solid electrolyte membrane prepared in this embodiment is used as the solid electrolyte. The impedance of the stainless steel blocking cell is tested by the EIS method. The ionic conductivity of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment at 20°C is about 2.54×10 -5 S / cm.

[0075] Example 2

[0076] A solid electrolyte membrane, the preparation process of which is as follows:

[0077] 1. Weigh 2.0 g of perfluoropolyether alcohol into a glass bottle, then move it into a glove box, and weigh 0.4 g of lithium bis(trifluoromethanesulfonylimide) and add it. Cover the bottle cap and place the glass bottle at room temperature with magnetic stirring for 1 hour to evenly disperse the lithium salt.

[0078] 2. Weigh 10.0g of fluorine-containing polymer and the above-mentioned perfluoropolyether alcohol and add them to an internal mixer for mixing to make the raw materials uniform. Add the uniformly mixed raw materials to a hot press and hot press them at 180°C and 20MPa for 40s to obtain a flame-retardant flexible solid electrolyte membrane (referred to as FFKM2-PFPE-OH-LiTFSI). Use a film press to cut the obtained electrolyte membrane into discs with a diameter of 16mm and place them in a glove box for standby use.

[0079] According to the measurement by the film thickness gauge, the thickness of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment is about 90um; the flame-retardant flexible solid electrolyte membrane prepared in this embodiment is subjected to a combustion test, and the test shows that the flame-retardant flexible solid electrolyte membrane prepared in this embodiment extinguishes itself immediately after leaving the fire.

[0080] The flame-retardant flexible solid electrolyte membrane prepared in this embodiment is used as the solid electrolyte. The impedance of the stainless steel blocking battery is tested by the EIS method. The ionic conductivity of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment at 20°C is calculated by the formula σ=L / (R*S) to be about 3.86×10 -5 S / cm.

[0081] Example 3

[0082] A solid electrolyte membrane, the preparation process of which is as follows:

[0083] 1. Weigh 3.0g of perfluoropolyether alcohol into a glass bottle, then move it into a glove box, and weigh 0.3g of lithium bis(trifluoromethanesulfonyl imide) and add it. Cover the bottle cap and place the glass bottle at room temperature with magnetic stirring for 1 hour to evenly disperse the lithium salt.

[0084] 2. Weigh 10.0g of fluorine-containing polymer and the above-mentioned perfluoropolyether alcohol and add them to an internal mixer for mixing to make the raw materials uniform. Add the uniformly mixed raw materials to a hot press and hot press them at 180°C and 20MPa for 40s to obtain a flame-retardant flexible solid electrolyte membrane (referred to as FFKM3-PFPE-OH-LiTFSI). Use a film press to cut the obtained electrolyte membrane into discs with a diameter of 16mm and place them in a glove box for standby use.

[0085] The flame retardant solid electrolyte membrane prepared in this embodiment is measured by a film thickness gauge and has a thickness of about 100 um. The flame retardant flexible solid electrolyte membrane prepared in this embodiment is subjected to a combustion test, and the test shows that the flame retardant flexible solid electrolyte membrane prepared in this embodiment extinguishes itself immediately after leaving the fire.

[0086] The flame-retardant flexible solid electrolyte membrane prepared in this embodiment is used as the solid electrolyte. The impedance of the stainless steel blocking cell is tested by the EIS method. The ionic conductivity of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment at 20°C is about 3.16×10 -5 S / cm.

[0087] Example 4

[0088] A solid electrolyte membrane, the preparation process of which is as follows:

[0089] 1. Weigh 3.0g of perfluoropolyether alcohol into a glass bottle, then move it into a glove box, and weigh 0.6g of lithium bis(trifluoromethanesulfonyl imide) and add it. Cover the bottle cap and place the glass bottle at room temperature with magnetic stirring for 1 hour to evenly disperse the lithium salt.

[0090] 2. Weigh 10.0g of fluorine-containing polymer and the above-mentioned perfluoropolyether alcohol and add them to an internal mixer for mixing to make the raw materials uniform. Add the uniformly mixed raw materials to a hot press and hot press them at 180°C and 20MPa for 40s to obtain a flame-retardant flexible solid electrolyte membrane (referred to as FFKM4-PFPE-OH-LiTFSI). Use a film press to cut the obtained electrolyte membrane into discs with a diameter of 16mm and place them in a glove box for standby use.

[0091] According to the measurement by a film thickness gauge, the thickness of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment is about 110 um. The flame-retardant flexible solid electrolyte membrane prepared in this embodiment is subjected to a combustion test. The test shows that the flame-retardant flexible solid electrolyte membrane prepared in this embodiment extinguishes itself immediately after leaving the fire.

[0092] The flame-retardant flexible solid electrolyte membrane prepared in this embodiment is used as the solid electrolyte. The impedance of the stainless steel blocking cell is tested by the EIS method. The ionic conductivity of the flame-retardant flexible solid electrolyte membrane prepared in this embodiment at 20°C is about 4.55×10 -5 S / cm.

[0093] Comparative Example 1

[0094] A solid electrolyte membrane, the preparation process of which is as follows:

[0095] 1. Weigh 2.0 g of perfluoropolyether alcohol into a glass bottle, then move it into a glove box, and weigh 0.4 g of lithium bis(trifluoromethanesulfonylimide) and add it. Cover the bottle cap and place the glass bottle at room temperature with magnetic stirring for 1 hour to evenly disperse the lithium salt.

[0096] 2. Weigh 10.0 g of polyethylene oxide (molecular weight 4*10 5 ), and added to the internal mixer together with the above-mentioned perfluoropolyether alcohol for mixing, so that the raw materials are mixed evenly. The mixed raw materials are added to the hot press, and hot pressed for 40 seconds at 180°C and 20MPa to obtain a solid electrolyte membrane (denoted as PEO-PFPE-OH-LiTFSI), and the obtained electrolyte membrane is cut into discs with a diameter of 16 mm by a film press and placed in a glove box for standby use.

[0097] Measured by a thin film thickness gauge, the thickness of the solid electrolyte membrane prepared in this embodiment is about 110um; the solid electrolyte membrane prepared in this comparative example is subjected to a combustion test, and the test shows that the polyethylene oxide solid electrolyte membrane prepared in this comparative example burns violently after encountering fire, and melt dripping occurs.

[0098] The polyethylene oxide solid electrolyte membrane prepared in this comparative example is used as the solid electrolyte. The impedance of the stainless steel blocking cell is tested by the EIS method. The ionic conductivity of the polyethylene oxide solid electrolyte membrane prepared in this comparative example at 20°C is calculated by the formula σ=L / (R*S) to be about 6.28×10 -6 S / cm.

[0099] The combustion heat release data of the fluorine-containing polymer flexible solid electrolyte membrane prepared in Example 1 and Example 2 and the polyethylene oxide solid electrolyte membrane prepared in Comparative Example 1 are compared in the table below.

[0100]

[0101] It can be seen from the above table that compared with the polyethylene oxide solid electrolyte membrane prepared in Comparative Example 1, the peak value of the heat release rate and the total heat release of the fluorinated polymer flexible solid electrolyte membrane prepared in Example 1 and Example 2 are reduced to varying degrees, and the temperature required to reach the maximum heat release rate is increased, which is highly consistent with the previous combustion test results.

[0102] Figure 2 The AC impedance comparison diagram of the fluorinated polymer flexible solid electrolyte membrane prepared in Example 1 and Example 2 and the polyethylene oxide solid electrolyte membrane prepared in Comparative Example 1 is shown in FIG. Figure 2 The results were analyzed and it was found that under the same conditions, the ionic conductivity of the solid electrolyte membrane prepared using fluorine-containing polymers was significantly higher than that of the solid electrolyte membrane prepared using polyethylene oxide, and as the amount of lithium salt added increased, its ionic conductivity also increased accordingly.

[0103] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0104] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple, respectively.

[0105] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a flame retardant flexible solid electrolyte material, characterized in that: The method comprises: dispersing a lithium salt in a perfluoropolyether alcohol to obtain a mixture; The mixture is used to modify the fluorine-containing polymer to obtain a flame-retardant flexible solid electrolyte.

2. The method for preparing a flame retardant flexible solid electrolyte material according to claim 1, characterized in that: The structural formula of the perfluoropolyether alcohol is: Wherein, n is any positive integer; and / or The number average molecular weight of the perfluoropolyether alcohol is 10 4 ~10 6 .

3. The method for preparing a flame retardant flexible solid electrolyte material according to claim 1, characterized in that: The structural formula of the fluorine-containing polymer is: Among them, R f At least one selected from -CF3, -CF2CF3, -CF2CF2CF3 and -CF2CF2CF2CF3; X is selected from at least one of -COOH, -CN, -OC6F5; and / or The number average molecular weight of the fluorine-containing polymer is 10 4 ~10 6 .

4. The method for preparing a flame retardant flexible solid electrolyte material according to claim 1, characterized in that: The lithium salt includes at least one of lithium bis(oxalatoborate), lithium difluoro(oxalatoborate), lithium bis(difluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide).

5. The method for preparing a flame retardant flexible solid electrolyte material according to claim 1, characterized in that: The mass ratio of the fluorine-containing polymer to the perfluoropolyether alcohol is 10:(2-3); and / or The mass ratio of the fluorine-containing polymer to the lithium salt is 10:(0.2-0.6).

6. The method for preparing a flame retardant flexible solid electrolyte material according to claim 1, characterized in that: The modification method is to use an internal mixer for mixing.

7. A flame retardant flexible solid electrolyte material, characterized in that: The flame retardant flexible solid electrolyte material is prepared by the method according to any one of claims 1 to 6.

8. A solid electrolyte membrane, characterized in that: The composition of the solid electrolyte membrane includes the flame retardant flexible solid electrolyte material according to claim 7; and / or The thickness of the solid electrolyte membrane is 50 μm to 200 μm.

9. A method for preparing a solid electrolyte membrane, characterized in that: The method comprises: Obtaining the flame-retardant flexible solid electrolyte material according to claim 7; The flame-retardant flexible solid electrolyte is subjected to hot pressing to form a film to obtain a solid electrolyte membrane.

10. The method for preparing a solid electrolyte membrane according to claim 9, characterized in that: The hot pressing temperature of the hot pressing film forming is 150°C to 230°C; and / or The hot pressing pressure of the hot pressing film forming is 15MPa to 20MPa; and / or The hot pressing time of the hot pressing film forming is 30s to 60s.

Citation Information

Patent Citations

  • Hybrid solid single-ion-conducting electrolytes for alkali batteries

    CN107534181A

  • Liquid electrolytes for lithium batteries

    CN109478681A

  • Solid electrolyte as well as preparation method and application thereof

    CN110048156A

  • Preparation method of organic flame-retardant electrolyte for lithium ion batteries

    CN111403810A

  • Electrolyte composition, gel polymer electrolyte, and lithium secondary battery including same

    CN116745951A

Cited By

  • Flame-retardant flexible solid electrolyte material, and preparation method therefor and use thereof

    WO2026077274A1